Encyclopedia of Hydrological Sciences 2005
DOI: 10.1002/0470848944.hsa172
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Englacial Drainage of Glaciers and Ice Sheets

Abstract: Supraglacial drainage occurs wherever snowpack, firn, or ice at the glacier surface is at the pressure melting point and supplied with additional energy, thereby generating melt water. Energy sources vary, but net radiation is usually the dominant source, although inputs of rainwater can also provide large volumes of surface runoff. The surface melt water is routed through the snowpack, firn, and across the glacier surface according to the local hydraulic gradient. In general, routing of water through snow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Second, supraglacial drainage networks generally evolve downglacier, with the proportion of smaller feeder channels gradually reducing relative to that of larger trunk channels, as the former merge into the latter. Thus, other things being equal, the greater the upglacier drainage 'fetch' above a sample site, the more discrete and less widespread the local drainage will be (Hodgkins, 1997;Nienow and Hubbard, 2005). As AB has a considerably longer fetch than ML or VB (Figure 1), it follows that the supraglacial drainage system is likely to be more discretely organized into fewer, larger channels in the area concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Second, supraglacial drainage networks generally evolve downglacier, with the proportion of smaller feeder channels gradually reducing relative to that of larger trunk channels, as the former merge into the latter. Thus, other things being equal, the greater the upglacier drainage 'fetch' above a sample site, the more discrete and less widespread the local drainage will be (Hodgkins, 1997;Nienow and Hubbard, 2005). As AB has a considerably longer fetch than ML or VB (Figure 1), it follows that the supraglacial drainage system is likely to be more discretely organized into fewer, larger channels in the area concerned.…”
Section: Discussionmentioning
confidence: 99%
“…In west Greenland, Poinar et al [52] observed a moulin density of 0.02 km −2 between 1500-and 1600-m elevations which compared with 12 km −2 at lower (0-1100 m) elevations [51]. This reduction in moulin density ensures that at high elevations, meltwaters are often transported considerable distances from the source of meltwater generation to the point of input to the englacial drainage system [34].…”
Section: Englacial Meltwater Processesmentioning
confidence: 97%
“…While storage of waters within the firn aquifer has only recently been revealed, the visible ponding of water in extensive supraglacial lakes has been known for decades [33,34] and their large size and the ready availability of satellite data has seen a marked increase in research on supraglacial lake development and drainage. These data reveal that lakes form seasonally in depressions in both the ablation and lower accumulation zones of the ice sheet [35], with their locations controlled by the underlying subglacial topography [36] or basal friction [37] thereby ensuring that they typically reform in the same location each year given sufficient surface meltwater.…”
Section: Supraglacial Meltwater Processesmentioning
confidence: 99%
“…This method assumes an impermeable surface with no storage and requires that sinks (low elevation pixels surrounded by higher elevation pixels) be leveled to force flow routing from drainage boundary to catchment outlet [39]. This processing step is problematic in ice surfaces, however, where surface water drains via moulins (sinks on the ice surface) to the englacial hydrological system [39][40][41]. Yang et al (2015) [34] and Rippin et al (2015) [4] both concluded that flow routing overestimates hydrological network extent for this reason.…”
Section: Introductionmentioning
confidence: 99%